A Feast in Carthage: Testing the Limits of 'Secularity' in Late Antiquity. (November 2020) - Gassman, Mattias P.
Abstract: A now conventional model, developed by Robert Markus, sees late Roman cities as fundamentally secular landscapes. Focusing on Augustine's sermon against a feast of the genius of Carthage ( Sermo 62), this article argues that narratives of 'secularity' have neglected pagans' own attitudes and the circumstances that drove ordinary Christians' participation in civic rites. Behind Augustine's charges of 'idolatry' lay the religious convictions of the feast's non-Christian sponsors and behind their expectations of Christian attendance lay the recent destruction of a pagan shrine on church property. For Augustine's listeners to construe the feast as religiously irrelevant was an expression not of routine social solidarity, but of fear before powerful patrons. What was 'secular' was open to doubt and negotiation, both here and in empire-wide celebrations such as the Kalends of January; the boundary between the 'pagan' and the 'secular' can be located only with careful attention to the diversity of opinions about each particular rite.